2011
DOI: 10.1128/aac.01402-10
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-Analysis of the Effectiveness and Safety of Tigecycline for Treatment of Infectious Disease

Abstract: The aim of this study was to compare the efficacy and safety of tigecycline, a newly developed glycylcycline antibiotic, with those of empirical antibiotic regimens which have been reported to possess good efficacy for complicated skin and skin structure infections (cSSSIs), complicated intra-abdominal infections (cIAIs), community-acquired pneumonia (CAP), and other infections caused by methicillin-resistant Staphylococcus aureus (MRSA) or vancomycin-resistant Enterococcus (VRE CI ‫؍‬ 0.69 to 1.07, P ‫؍‬ 0.19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
103
2
10

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(119 citation statements)
references
References 51 publications
4
103
2
10
Order By: Relevance
“…Yahav et al [3] meta-analysis reported statistically higher all-cause 30-day mortality in the tigecycline arms. On the other hand, Cai et al [4] found no difference in all-cause mortality and drug-related mortality between tigecycline and the comparators, whereas Tasina et al [5] demonstrated reduced clinical efficacy and increased mortality for tigecycline, but the difference was not statistically significant. The FDA alert has been further jeopardized by two more studies.…”
mentioning
confidence: 97%
“…Yahav et al [3] meta-analysis reported statistically higher all-cause 30-day mortality in the tigecycline arms. On the other hand, Cai et al [4] found no difference in all-cause mortality and drug-related mortality between tigecycline and the comparators, whereas Tasina et al [5] demonstrated reduced clinical efficacy and increased mortality for tigecycline, but the difference was not statistically significant. The FDA alert has been further jeopardized by two more studies.…”
mentioning
confidence: 97%
“…47 Tigecycline use has been associated with higher all cause mortality rates, though it was not statistically significant, FDA has issued a warning. 48 No dosage adjustment of tigecycline is necessary in patients with renal insufficiency or mild to moderate hepatic impairment and the aged population, although in patients with severe hepatic impairment, the initial dose should be 100 mg, followed by a reduced maintenance dose of 25 mg every 12 hrs. 49 …”
Section: Tigecyclinementioning
confidence: 99%
“…and Morganella spp. 22,38,54,55 However, evidence of increased mortality, compared to other antibiotic therapies, especially in ventilator-associated pneumonia 48 leads to caution in its use. Moreover, a serious drawback, at least for monotherapy in bacteremia, is the low serum level obtained.…”
Section: Tigecyclinementioning
confidence: 99%